ZRF1 is a novel S6 kinase substrate that drives the senescence programme. (27th February 2017) - Barilari, Manuela; Bonfils, Gregory; Treins, Caroline; Koka, Vonda; De Villeneuve, Delphine; Fabrega, Sylvie; Pende, Mario
Abstract: The inactivation of S6 kinases mimics several aspects of caloric restriction, including small body size, increased insulin sensitivity and longevity. However, the impact of S6 kinase activity on cellular senescence remains to be established. Here, we show that the constitutive activation of mammalian target of rapamycin complex 1 (mTORC1) by tuberous sclerosis complex (TSC) mutations induces a premature senescence programme in fibroblasts that relies on S6 kinases. To determine novel molecular targets linking S6 kinase activation to the control of senescence, we set up a chemical genetic screen, leading to the identification of the nuclear epigenetic factor ZRF1 (also known as DNAJC2, MIDA1, Mpp11). S6 kinases phosphorylate ZRF1 on Ser47 in cultured cells and in mammalian tissues in vivo . Knock‐down of ZRF1 or expression of a phosphorylation mutant is sufficient to blunt the S6 kinase‐dependent senescence programme. This is traced by a sharp alteration in p16 levels, the cell cycle inhibitor and a master regulator of senescence. Our findings reveal a mechanism by which nutrient sensing pathways impact on cell senescence through the activation of mTORC1‐S6 kinases and the phosphorylation of ZRF1. Synopsis: Aberrant mTORC1 signalling induces cell senescence via S6 kinase‐mediated phosphorylation of epigenetic factor ZRF1, thereby linking nutritional cues to regulation of cell fitness. S6 kinases are required for the senescence programme triggered by constitutive mTORC1 activation. S6 kinases selectively regulate the p16 cell cycle inhibitor, without affecting the p53/p21‐dependent response. A chemical genetic screen uncovers the epigenetic factor ZRF1 as a novel S6 kinase substrate, whose phosphorylation is triggered by nutritional cues and mTORC1 activity. ZRF1 phosphorylation by S6 kinases participates in the senescence response. Abstract : Aberrant mTORC1 signalling induces cell senescence via S6 kinase‐mediated phosphorylation of epigenetic factor ZRF1, thereby linking nutritional cues to regulation of cell fitness.